2007
DOI: 10.1002/adma.200601310
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Carboxylated Carbonaceous Fragments in the Functionalization and Spectroscopy of a Single‐Walled Carbon‐Nanotube Material

Abstract: The majority of carboxylic acid groups formed after treatment of a single‐walled carbon nanotube (SWCNT) material with nitric acid are present on carboxylated carbonaceous fragments (CCFs) (see figure). These CCFs are removed from the SWCNTs by treatment with NaOH solution and identified as carriers of the COOH functionality, implying that previous reports claiming side‐wall functionalization of the SWCNTs with COOH groups should be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
221
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(236 citation statements)
references
References 36 publications
8
221
1
5
Order By: Relevance
“…In previous reports, it has been observed that high temperature oxidation treatments using HNO 3 on SWCNTs may generate carbonaceous debris adsorbed on the nanotubes surface containing the great majority of carboxylic groups [40]. This carbonaceous material (also known as fulvic acid) has also been observed in oxidized MWCNTs [41,42] which was then removed after a basic treatment with NaOH, thus decreasing the amount of functional groups anchored to the CNT sidewalls.…”
Section: Resultsmentioning
confidence: 97%
“…In previous reports, it has been observed that high temperature oxidation treatments using HNO 3 on SWCNTs may generate carbonaceous debris adsorbed on the nanotubes surface containing the great majority of carboxylic groups [40]. This carbonaceous material (also known as fulvic acid) has also been observed in oxidized MWCNTs [41,42] which was then removed after a basic treatment with NaOH, thus decreasing the amount of functional groups anchored to the CNT sidewalls.…”
Section: Resultsmentioning
confidence: 97%
“…The chemical and thermal treatments used during functionalization can affect the nature and concentration of the surface functional groups displayed. Note that however, it is also likely that the presence of fulvic acids during the nitric acid functionalization of the filter could result in additional oxygen groups on the CNT surface, which also contributed to the adsorption process [29][30][31]. Base wash is an effective approach for completely neutralizing this effect which has not been considered in present work.…”
Section: Metal Ion Removalmentioning
confidence: 95%
“…No caso da purificação já é bem conhecido que a remoção dessas impurezas pode ser conduzida em grandes quantidades, porém a eliminação efetiva das várias impurezas depende muito da metodologia aplicada e esta quando não realizada com cuidado pode provocar uma série de defeitos estruturais, fracionamento e/ ou destruição dos NTCs. 112,113 Dependendo do fornecedor ou do método usado na produção dos NTCs várias nanoestruturas podem estar presentes e os métodos de purificação nem sempre podem ser estendidos para qualquer tipo de amostra, pois a eficiência das metodologias pode depender muito das impurezas e do tipo de NTC da amostra. Por exemplo, a ação do ácido nítrico concentrado sobre os NTCs depende do seu diâmetro, densidade de defeitos, presença ou não de carbono amorfo, do empilhamento e número de camadas de grafeno que constituem a sua superfície.…”
Section: Nanotubos De Carbono E Suas Impurezasunclassified
“…Por exemplo, NTCPM hidrofóbicos sem processamento pós-síntese apresentam menor toxicidade do que esta mesma amostra tratada com ácido nítrico. 117 Essas variáveis também se aplicam para as várias metodologias de funcionalização, já que mesmo com os avanços obtidos a maioria dos tratamentos químicos pode gerar resíduos, fragmentos de tubos oxidados e fragmentos de carbonos carboxilados denominados debris, 112,113 ou outras nanoestruturas. Por exemplo, o uso de ácido nítrico concentrado pode gerar fragmentos de carbonos carboxilados debris, principalmente quando durante o processo de purificação não se remove o carbono amorfo das paredes dos tubos.…”
Section: Nanotubos De Carbono E Suas Impurezasunclassified
See 1 more Smart Citation